DOI: 10.1007/978-3-540-70545-1_40
|View full text |Cite
|
Sign up to set email alerts
|

Jakstab: A Static Analysis Platform for Binaries

Abstract: For processing compiled code, model checkers require accurate model extraction from binaries. We present our fully configurable binary analysis platform JAKSTAB, which resolves indirect branches by multiple rounds of disassem-bly interleaved with dataflow analysis. We demonstrate that this iterative disassembling strategy achieves better results than the state-of-the-art tool IDA Pro. Introduction. While most of today's model checkers operate on source code, there are various settings where we need to verify b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
84
0

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 108 publications
(89 citation statements)
references
References 7 publications
0
84
0
Order By: Relevance
“…Earlier work [1,5,3,7,6] has shown that data flow analysis can be used to augment the results of disassembly, but no conclusive answer was given on the best way to handle states with unresolved control flow successors during data flow analysis. Further, updating the control flow graph could render previous data flow information invalid, which would require backtracking and could cause the analysis to diverge.…”
Section: Augmenting Disassembly With Data Flow Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Earlier work [1,5,3,7,6] has shown that data flow analysis can be used to augment the results of disassembly, but no conclusive answer was given on the best way to handle states with unresolved control flow successors during data flow analysis. Further, updating the control flow graph could render previous data flow information invalid, which would require backtracking and could cause the analysis to diverge.…”
Section: Augmenting Disassembly With Data Flow Analysismentioning
confidence: 99%
“…We implemented the worklist algorithm for control flow reconstruction (Algorithm 2) in our disassembly and static analysis tool JAKSTAB [6]. JAKSTAB works on X86 executables, and translates them into an intermediate language that is similar in style but more complex than JUMP.…”
Section: Instantiation Of the Framework In The Jakstab Toolmentioning
confidence: 99%
See 2 more Smart Citations
“…These mostly spurious edges introduce additional imprecision into the analysis as abstract states propagate across them, in the end yielding a degenerate CFG that is unusable for analysis. In practice, existing tools [13] therefore either immediately report an error whenever they cannot resolve an indirect branch or simply turn the indirect jump into a leaf without any successors.…”
Section: Introductionmentioning
confidence: 99%